Improving Students' Conceptual Understanding and Collaboration Skills in Ecology Learning through Educational Snakes and Ladders Media - Yusi Avrillia Putri; Dede Nuraida (Postgraduate, University of Mataram, 2026)
This study aims to examine the improvement in students' conceptual understanding and collaboration skills following the implementation of the Snakes and Ladder media in ecology lessons. The material covered ecology and ecosystems, ecosystem components, interactions between living organisms, ecosystem balance, and ecosystem pollution. A quantitative approach with a one-group pretest-posttest pre-experimental design was employed. The research subjects were 28 students from class VII D at SMPN 2 Tuban. Conceptual understanding was measured using essay tests administered as a pretest before instruction and a posttest after instruction. Meanwhile, collaboration skills were assessed via questionnaires administered before and after the lessons involving the Snakes and Ladder media. Data on conceptual understanding were analyzed using descriptive statistics and normalized gain (N-gain) analysis. Collaboration skill data were analyzed descriptively by calculating percentage scores and categorizing them based on established criteria. The results showed that the average conceptual understanding score increased from 35.25 to 58.96, with an N-gain value of 0.37 (indicating a moderate improvement). Students' collaboration skills also improved from 63.00% (fair category) to 77.85% (good category). These findings indicate that implementing the